Biracial Discrimination Recounted: A Deep Dive into The Meaning of Mariah Carey - Putri, Erischa Rahayu; Adhitya, Galant Nanta; Kristiawan, Yohanes Angie (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
Mariah Carey is an American singer and songwriter; whose mother is white, but her father is black. In 2020, she released The Meaning of Mariah Carey retracks Carey’s life as a biracial woman. This article explains how she is discriminated and reacts to the discrimination. The theories employed are Post-National American Studies; Blank, Dabady, and Citro’s types of discrimination; and Aguirre and Turner’s reaction to discrimination. When she was a kid, teenager, and young adult, the discrimination she endures is more intentional and explicit. The discrimination becomes subtler and more indirect, as she has cemented her status as a musical icon. The fact that she is still discriminated even after she has reached the peak of her superstardom suggests that biracial discrimination can happen to any mixed-race person, regardless of their socioeconomic class. Discrimination comes from both sides of the race. The article signifies how the discrimination faced by mixed-raced people are both similar, but also different from the experiences of other minorities.